Growth and biochemical responses of vetiver grass (Vetiveria zizanioides) to magnetized water and Pb - HOODAJI, MEHRAN; HAFSHAJANI, ELAHE JAFARI; GHANATI, FAEZEH; HOSSEINI, YAGHOOB; ALIPOUR, VALI (The Indian Journal of Agricultural Sciences, 2022)
An experiment was conducted to evaluate the phytoremediation efficiency, growth and biochemical responses of vetiver grass (Vetiveria Zizanioides) in response to irrigation with magnetized water [in 3 levels including magnetized water, semi-magnetized water and non-magnetized water] and Pb from the source of Pb-Nitrate salt [in 4 levels including 0, 5, 10 and 20 mg/L). This study was carried out as a factorial arrangement based on a completely randomized design with three replications in the central nursery of Green Area and Parks Organization Bandar Abbas Municipality, Bandar Abbas, Iran, during 2020–21. A magnetic water generating device called a magnetic ion stirrer with an intensity of 110 Tesla was used in this study. The results showed that irrigation with the magnetized water significantly increased the growth and yield of vetiver, and uptake and translocation factor of Pb to the shoots. Increase in the activities of enzymatic antioxidants affected by the magnetized water was observed which led to the production of reactive oxygen species (ROS) and activated the plant defense system. In general, despite high accumulation of Pb in plant tissues evident from accumulation of ROS, but still vetiver growth and yield were not significantly affected, indicating the phyto-toxic tolerance of vetivar against Pb accumulation. It is concluded that irrigation with the magnetized water through stimulating the antioxidants of vetiver can improve the growth, yield, uptake and translocation of Pb and therewith increases the phytoremediation efficiency of Vetiver.